A Review on Hybrid Magnetorheological Isolator - Firdaus Jaafar, Mohd; Iqmal Mohd Razali, Zarul; Amirani Ahmad, Nur (International Journal of Engineering and Technology, 2018)
Hybrid magnetorheological elastomer-fluid (MRE-F) isolator is a device used to bridge the limitations impose from the magnetorheological elastomer (MRE) or magnetorheological fluid (MRF) alone.  MRE is known to perform better in terms of isolating vibration by stiffness changes (it’s a stiffness dominant device) where as MRF is known to have problem with sedimentation of magnetizable particles due to gravity. A composite of MRE and MRF will bring the benefit of both domains into a single isolator device. Magnetorheological properties from hybrid MRE-F can be further improve by examining the various factors affecting the overall performance of the hybrid isolator.